Risk of ischaemic and haemorrhagic stroke in Chinese undergoing percutaneous coronary intervention treated with potent P2Y12 inhibitor versus clopidogrel. Issue 4 (9th March 2022) - Ng, Andrew Kei-Yan; Ng, Pauline Yeung; Ip, April; Lau, Kui Kai; Siu, Chung-Wah
Abstract : Background: Stroke after acute coronary syndrome (ACS) can be devastating. It is uncertain whether the risks of ischaemic stroke or intracranial haemorrhage (ICH) are associated with different choices of P2Y12 inhibitors (potent P2Y12 inhibitors such as ticagrelor and prasugrel vs clopidogrel). Even though East Asians are known to have different thrombotic and haemorrhagic profiles from Caucasians, data on Chinese patients are sparse. Method: This was a retrospective cohort study conducting in Chinese patients with ACS who underwent first-ever percutaneous coronary intervention from 14 hospitals in Hong Kong between 2010 and 2017. The primary efficacy endpoint was ischaemic stroke. The secondary efficacy endpoint was a composite outcome of thrombotic events including all-cause mortality, non-fatal myocardial infarction and ischaemic stroke. The primary safety endpoint was ICH. The secondary safety endpoint was a composite of major bleeding events. Results: After adjustment of baseline characteristics by 1:1 propensity score matching, a total of 6220 patients (3110 on each group) were analysed. Compared with clopidogrel, potent P2Y12 inhibitors were associated with a lower risk of ischaemic stroke (HR 0.57; 95% CI 0.37 to 0.87; p=0.008) and a lower risk of thrombotic events (HR 0.77; 95% CI 0.66 to 0.90; p=0.001). Potent P2Y12 inhibitor was associated with similar risk of ICH (HR 0.65; 95% CI 0.34 to 1.25, p=0.20) and major bleeding (HR 0.83; 95% CI 0.68 to 1.01, p=0.069). Conclusions: Potent P2Y12 inhibitors were associated with a lower adjusted risk of ischaemic stroke and thrombotic events, compared with clopidogrel. The risks of ICH and major bleeding were similar.